Revisiting money demand in Malaysia : simple-sum versus divisia monetary aggregates - Puah, Chin-Hong; Leong, Choi-Meng; Abu Mansor Shazali,; Lau, Evan (Penerbit Universiti Kebangsaan Malaysia, 2018)
BNM has discarded the use of monetary targeting due to the speeding up of financial reforms as the relationship between money and important macroeconomic indicators in Malaysia has weakened. However, the implementation of the interest rate targeting requires the authorities to alter the policy rate recurrently. Alternatively, the authorities may consider monetary targeting, which provides the ease of control of monetary aggregates, provided that a stable demand for money function can be derived. Nevertheless, financial liberalization has greatly affected the stability of money demand. Thus, this study estimated the demand for money function in Malaysia by considering the effect of the financial development in which a Divisia monetary aggregate has been constructed as an alternative measure of money and a monetization variable has been included in the function. The Johansen and Juselius cointegration test and error correction model are utilized to estimate the demand for money function. The empirical findings indicate that a plausible demand for money function is derived using Divisia M2. Furthermore, monetization appears as an important variable that contributes to a stable money demand. The presence of a stable Divisia M2 money demand has reassured the usefulness of monetary aggregate as the indicator for monetary policy purposes. Monetary targeting provides alternative policy target choice for the conduct of monetary policy. Divisia monetary aggregates can also serve as the alternative money measurement apart from the conventional money supply.